Physiological and molecular insight of microbial biostimulants for sustainable agriculture - Kaushal, Priya; Ali, Nilofer; Saini, Shivani; Pati, Pratap Kumar; Pati, Aparna Maitra (Frontiers in Plant Science, 2023)
Increased food production to cater the need of growing population is one of the major global challenges. Currently, agro-productivity is under threat due to shrinking arable land, increased anthropogenic activities and changes in the climate leading to frequent flash floods, prolonged droughts and sudden fluctuation of temperature. Further, warm climatic conditions increase disease and pest incidences, ultimately reducing crop yield. Hence, collaborated global efforts are required to adopt environmentally safe and sustainable agro practices to boost crop growth and productivity. Biostimulants appear as a promising means to improve growth of plants even under stressful conditions. Among various categories of biostimulants, microbial biostimulants are composed of microorganisms such as plant growth-promoting rhizobacteria (PGPR) and/or microbes which stimulate nutrient uptake, produce secondary metabolites, siderophores, hormones and organic acids, participate in nitrogen fixation, imparts stress tolerance, enhance crop quality and yield when applied to the plants. Though numerous studies convincingly elucidate the positive effects of PGPR-based biostimulants on plants, yet information is meagre regarding the mechanism of action and the key signaling pathways (plant hormone modulations, expression of pathogenesis-related proteins, antioxidants, osmolytes, etc.) triggered by these biostimulants in plants. Hence, the present review focuses on the molecular pathways activated by PGPR based biostimulants in plants facing abiotic and biotic challenges. The review also analyses the common mechanisms modulated by these biostimulants in plants to combat abiotic and biotic stresses. Further, the review highlights the traits that have been modified through transgenic approach leading to physiological responses akin to the application of PGPR in the target plants.